Development of a multicellular pancreatic tumor microenvironment system using patient-derived tumor cells. Issue 7 (6th March 2019) - Gioeli, Daniel; Snow, Chelsi J.; Simmers, Michael B.; Hoang, Stephen A.; Figler, Robert A.; Allende, J. Ashe; Roller, Devin G.; Parsons, J. Thomas; Wulfkuhle, Julia D.; Petricoin, Emanuel F.; Bauer, Todd W.; Wamhoff, Brian R.
Abstract : The development of drugs to treat cancer is hampered by the inefficiency of translating pre-clinical in vitro monoculture and mouse studies into clinical benefit. Abstract : The development of drugs to treat cancer is hampered by the inefficiency of translating pre-clinical in vitro monoculture and mouse studies into clinical benefit. There is a critical need to improve the accuracy of evaluating pre-clinical drug efficacy through the development of more physiologically relevant models. In this study, a human triculture 3D in vitro tumor microenvironment system (TMES) was engineered to accurately mimic the tumor microenvironment. The TMES recapitulates tumor hemodynamics and biological transport with co-cultured human microvascular endothelial cells, pancreatic ductal adenocarcinoma, and pancreatic stellate cells. We demonstrate that significant tumor cell transcriptomic changes occur in the TMES that correlate with the in vivo xenograft and patient transcriptome. Treatment with therapeutically relevant doses of chemotherapeutics yields responses paralleling the patients' clinical responses. Thus, this model provides a unique platform to rigorously evaluate novel therapies and is amenable to using patient tumor material directly, with applicability for patient avatars.